PARTISIPASI LANSIA DALAM PENGELOLAAN HOMESTAY: STUDI KASUS HOMESTAY KARANG KEDEMPEL DI DESA WISATA KARANGSAMBUNG - Fira Ananta Sujawoto; Rifki Rahmanda Putra; Herlan Suherlan; Nurdin Hidayah; R. Fajar Widiarrachman (Jurnal Pariwisata Budaya: Jurnal Ilmiah Pariwisata Agama dan Budaya, 2025)
The presence of homestays in tourist villages can be one of the main means for community empowerment, including those in the elderly or elderly category. The stay experience offered by homestays in tourist villages is not limited to one-way service, but also seeks two-way interaction between the manager and the guests staying. This research aims to explore the role and active participation of the elderly in the management of Karang Kedempel Homestay in Karangsambung Tourism Village. This homestay is directly managed by a 73-year-old elderly person, who offers a different stay experience for the tourists. In the management of this homestay, the elderly not only act as managers, but also as preservers of the principles and values of local wisdom. Therefore, this research seeks to explore in depth how the elderly apply their principles and motivations in the management of homestays, as well as analyze the challenges and socio-economic impacts brought about by the presence of homestays.